Analisis Pengaruh Sektor Industri Pengolahan Terhadap Pertumbuhan Ekonomi Di Kabupaten Sijunjung - Nuri Latifannisa; Marwan Marwan (Jurnal Salingka Nagari, 2023)
The goal of this study is to look into the correlation between the manufacturing sector's employment rate, investment, and company count and the region of Sijunjung's economic growth. The Central Statistics Agency of Sijunjung Regency is the data source for this type of descriptive associative research, which employs secondary data. The study's timescale included the years 1992 until 2021. Multiple linear regression analysis is the analytical technique used. To the analysis's results, Sijunjung Regency's economic growth is negative and insignificantly affected by the variable number of manufacturing companies, positive and significant growth is affected by manufacturing sector's investment variable and positive and significantly by manufacturing sector's worker variable. The economy of Sijunjung Regency and the results of the model's estimation reveal that the variables of investment, employment, and company count all have an impact on the region's economic growth.